2021
DOI: 10.3389/fphar.2021.628526
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate, the Main Polyphenol in Green Tea, Inhibits Porcine Epidemic Diarrhea Virus In Vitro

Abstract: There are currently no licensed drugs against porcine epidemic diarrhea virus (PEDV), but vaccines are available. We identified a natural molecule, epigallocatechin-3-gallate (EGCG), the main polyphenol in green tea, which is effective against infection with PEDV. We used a variety of methods to test its effects on PEDV in Vero cells. Our experiments show that EGCG can effectively inhibit PEDV infections (with HLJBY and CV777 strains) at different time points in the infection using western blot analysis. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Our previous studies have shown that the small molecular medicine EGCG can inhibit PRV and PEDV adsorption, entry, and replication [ 20 , 40 ]. However, most of the small molecule medicines can only act on a single target.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that the small molecular medicine EGCG can inhibit PRV and PEDV adsorption, entry, and replication [ 20 , 40 ]. However, most of the small molecule medicines can only act on a single target.…”
Section: Discussionmentioning
confidence: 99%
“…Salinomycin [ 39 ] and remdesivir [ 40 ] have been reported as potential antiviral drugs against PEDV infection in vitro. Several natural products extracted from plants, such as glycyrrhizin [ 16 ], quercetin 7-rhamnoside [ 15 ], and epigallocatechin-3-gallate [ 41 ], have been demonstrated to reduce PEDV infection in Vero cells. To search for new anti-PEDV agents, Deejai et al screened the FDA-approved drugs that could associate with the PEDV N protein using virtual screening and found that trichlormethiazide, D-(+) biotin and acetazolamide could inhibit PEDV replication in vitro [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hemolytic activity and mammalian cell cytotoxicity of metformin in combination with minocycline was evaluated based on previously reported studies [ 46 , 52 ]. For hemolytic activity assay, 8% sheep blood cells (Yuanye, Shanghai, China) prepared from fresh sterile defibrinated sheep blood was treated with a combination of minocycline (16–128 µg/mL) and metformin (0–80 mg/mL), using 0.2% Triton X-100 as a positive control and PBS (0.01 mol/L, pH = 7.4) as a negative control at 37 °C for one hour followed by the measurement of the released hemoglobin absorption at 576 nm by Bio-Tek Synergy2 Multi-mode Microplate Reader.…”
Section: Methodsmentioning
confidence: 99%